Capital requirement, bank competition and stability in Africa - Jacob Oduor; Kethi Ngoka; Maureen Odongo (Review of Development Finance, 2017)
Monetary authorities around the world are implementing enhanced banking capital adequacy requirements under Basel III meant to improve financial stability. Critics however argue that increased capital requirements concentrate the banking industry reducing competition while not guaranteeing financial sector stability. Using data from 167 banks in 37 African countries, we find that increased capital beef-up significantly increases financial instability in Africa (except in big banks) implying that higher capital requirements did not make African banks safer. We also find that increased regulatory capital improves competitive pricing for foreign banks while it makes domestic banks less competitive mainly attributed to the high cost of sourcing and holding extra capital for domestic banks compared to foreign banks who can source cheaper capital from parent companies. The results put to question the effectiveness of enhanced regulatory capital on stability and competitiveness of the African financial system.
Keywords: E44; G01; G21; G28; 650; Financial stability; Banking competition; Capital requirements